The psychology of learning and motivation : advances in research and theory. - Busemeyer, Jerome R.; Hastie, Reid; Medin, Douglas L. (Psychology of learning and motivation ;, 1995)
The Psychology of Learning and Motivation publishes empirical and theoretical contributions in cognitive and experimental psychology, ranging from classical and instrumental conditioning to complex learning and problem solving. This guest-edited special issue is devoted to research and discussion on decision making from a cognitive perspective. Topics include judgment and decision making with respect to memory processes and techniques, domain-specificity, and confirmation bias. Key Features * Synthesis of decision and cognitive research * New theoretical treatments of critical phenomena * New findings and systematic reviews of past work * Coverage of preference, inference, prediction, and hypothesis-testing * Written by the new leading generation of researchers.